Using BioDepot-workflow-builder to Access Public Databases in a Containerized Environment - Scott, Christin; Hung, Ling-Hong; Lloyd, Wes; Yeung, Ka Yee (2019 IEEE International Conference on Bioinformatics and Biomedicine (BIBM), 2019)
Modern day analyses of biomedical data typically involves a series of computational tasks called workflows. Each of these modules could be written by different laboratories and thus, potentially requires different computing environments. Reproducible analyses of biomedical data is a growing field of interest [1]. This makes it important to develop tools to facilitate analyses in a reproducible manner. Software containers have been used to increase reproducibility in bioinformatics analyses [2]. However, these software containers often use command line tools, requiring expertise that make them inaccessible to many biomedical scientists.